2018
DOI: 10.1002/hpm.2572
|View full text |Cite
|
Sign up to set email alerts
|

Who wants to pay more taxes to improve public health care?

Abstract: We study the factors that influence willingness to pay to improve public health care in 29 post-communist countries, Eastern and Southern Europe, and Eurasia using 2 up-to-date cross-sectional surveys conducted in 2010 and 2016 (N = 34 768). Three hypotheses received full degree of support through empirical analysis: increase in satisfaction with health care, university education, and higher level of wealth positively associated with willingness to pay in all regions. In comparison, having a higher level socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…More specifically, I probe attitudes towards increasing health care spending during the Corona pandemic by making use of novel survey data for Germany collected in three waves in April/May and November 2020 as well as May 2021. The paper speaks to recent scholarship on the relationship between trust, performance perceptions and willingness to pay for social policy (Habibov et al, 2018a(Habibov et al, , 2018bRoosma et al, 2014;Van Oorschot & Meuleman, 2012). It can also build on and expand existing work on determinants of individual-level attitudes towards health care (Jensen, 2011(Jensen, , 2012Missinne et al, 2013;Naumann, 2014;Wendt et al, 2010;Wendt et al, 2011), which has provided a wealth of insights about the individual (self-interest, ideology) and institutional determinants of attitudes.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…More specifically, I probe attitudes towards increasing health care spending during the Corona pandemic by making use of novel survey data for Germany collected in three waves in April/May and November 2020 as well as May 2021. The paper speaks to recent scholarship on the relationship between trust, performance perceptions and willingness to pay for social policy (Habibov et al, 2018a(Habibov et al, , 2018bRoosma et al, 2014;Van Oorschot & Meuleman, 2012). It can also build on and expand existing work on determinants of individual-level attitudes towards health care (Jensen, 2011(Jensen, , 2012Missinne et al, 2013;Naumann, 2014;Wendt et al, 2010;Wendt et al, 2011), which has provided a wealth of insights about the individual (self-interest, ideology) and institutional determinants of attitudes.…”
Section: Introductionmentioning
confidence: 87%
“…There is a rich literature on the complex association between political trust and welfare state support that can only be briefly reviewed here (see Kumlin et al (2017) for a recent and more comprehensive overview). Generally speaking, researchers have identified a positive, self-reinforcing feedback relationship between political trust and more specific measures of welfare state performance on the one hand and individual willingness to support the welfare state and its further expansion on the other (Edlund, 2006;Gabriel & Trüdinger, 2011;Habibov et al, 2018aHabibov et al, , 2018bHabibov et al, 2019b;Hetherington, 2005;Kumlin, 2013;Lynch & Gollust, 2010;Rothstein et al, 2012;Rudolph & Evans, 2005;Svallfors, 2002;Wendt et al, 2010). Scholarship has studied both how generalized political trust might influence further support for the welfare state (Rothstein et al, 2012) as well as how performance perceptions of particular social policies in turn might increase general political trust (Cammett et al, 2016).…”
Section: Performance Perceptions Political Trust and Willingness To Spendmentioning
confidence: 99%
See 1 more Smart Citation
“…Lynch and Gollust (2010), using survey data from the US, argue that individual beliefs and perceptions of the fairness of the healthcare system matter more as determinants of policy preferences than indicators of self-interesta finding that is most relevant in the context of this article. In a string of articles that focus on Eastern European countries, Habibov and co-authors have shown that prevailing levels of institutional and social trust as well as individual perceptions of the quality of healthcare are systematically related to willingness to pay more taxes for healthcare provision (Habibov et al, 2017(Habibov et al, , 2018a(Habibov et al, , 2018b(Habibov et al, , 2019.…”
Section: Trust and The Welfare Statementioning
confidence: 99%
“…Apart from dimensions of safety, effectiveness, responsiveness, affordability, accessibility, and patient-centeredness [15][16][17][18][19][20], public satisfaction is also a very important comprehensive indicator of the health system [1,6,14], because it includes not only users (the patients) but also non-users (the healthy population) in the system [7]. Hence, it can provide meaningful information (such as key factors of public satisfaction improvement) for health policy reform [21,22] and government's decisions making (such as fiscal expenditure allocation and healthcare service supplies) [23][24][25][26]. Since governments in modern societies usually play key roles in the health systems [6,14], the public's satisfaction with the health system is closely associated with the public satisfaction with and public trust in governments [23].…”
Section: Introduction 1healthcare Satisfactionmentioning
confidence: 99%